2005
DOI: 10.1097/01.mlr.0000156864.80880.aa
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnic Disparities in Utilization of Lifesaving Technologies by Medicare Ischemic Heart Disease Beneficiaries

Abstract: Despite having similar Medicare health insurance coverage, elderly utilization and IHD mortality rates differ markedly not only between whites and minorities, but within minority groups themselves. A large, nationally representative survey of physicians and patients is needed to distinguish between systemwide "failures to refer" and patient "aversions to surgery" as explanations for lower black rates of surgical interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…1212 Moreover, African Americans and Hispanics are 10% to 40% less likely to receive outpatient secondary prevention therapies for cardiovascular disease. 1213 Although lower rates of diagnostic and interventional services have not been adequately explained, 1214,1215 it is clear that individuals of lower socioeconomic status and ethnic minorities typically have fewer healthcare resources, have worse general health and cardiac risk profiles, and are less knowledgeable about SIHD symptoms. Healthcare providers and systems should strive to eliminate or ameliorate barriers to care for patients who have SIHD and are of low socioeconomic class or ethnic minorities.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…1212 Moreover, African Americans and Hispanics are 10% to 40% less likely to receive outpatient secondary prevention therapies for cardiovascular disease. 1213 Although lower rates of diagnostic and interventional services have not been adequately explained, 1214,1215 it is clear that individuals of lower socioeconomic status and ethnic minorities typically have fewer healthcare resources, have worse general health and cardiac risk profiles, and are less knowledgeable about SIHD symptoms. Healthcare providers and systems should strive to eliminate or ameliorate barriers to care for patients who have SIHD and are of low socioeconomic class or ethnic minorities.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…8 Black and American Indian patients were much less likely to undergo revascularization procedures, and these groups, as well as Hispanic and Asian patients, derived substantially lower survival benefits on average than white patients, raising provocative questions about why these differences arise despite Medicare insurance coverage and comparable access to hospitals performing these procedures. Similarly, a recent study we conducted found that insurance coverage was associated with substantial reductions in mortality for near-elderly white adults but not for a comparable cohort of black adults.…”
mentioning
confidence: 98%
“…2 The study examines residential and hospital racial segregation and evaluates their relationship to the use of high-mortality hospitals, after accounting for the influence of income and geographic proximity.…”
mentioning
confidence: 99%